Transcriptome and chemical analysis of healthy and infected stems of aquilaria malaccensis - Aimi-Wahidah, A.; Rofiza, M.; Saiful-Nizam, T.; Aizi-Nor-Mazila, R. (Forest Research Institute Malaysia, 2021)
Aquilaria genus is an important source of agarwood and is widely used as incense, perfumery and ingredients in traditional medicines. The study investigated the genes and pathways controlling the molecular mechanism of A. malaccensis agarwood under controlled environment. Two transcriptome libraries were sequenced from mRNAs of both healthy and infected stem samples of A. malaccensis using Illumina sequencing. Total of 10,734,590 and 8,298,918 reads for both infected stems libraries and 6,274,184 reads for healthy stem library were identified. A total of 370,707 unigenes were functionally annotated using the gene ontology analysis. Infected white stem recorded higher reading of unigenes distribution in process related to plant defence mechanism compared to healthy stem. The de novo assembly and the gene ontology annotation data suggested that the infected white stem involved in plant defence response and produced agarwood compound. This study provided promising and valuable sequence resources for future genomic studies from stem of A. malaccensis as well as in depth study on molecular mechanism of agarwood formation and plant related defence responses.